Multi-element synergistic flame-retardant water-based composite emulsion as well as preparation method and application thereof
By using a multi-element synergistic flame-retardant waterborne composite emulsion, combined with silicon, phosphorus, nitrogen, and boron elements and boron-containing cellulose-based reinforcing agents, the problem of balancing the flame-retardant performance and film strength of waterborne emulsions has been solved, achieving efficient flame retardancy and improved mechanical properties, making it suitable for high-requirement scenarios.
Patent Information
- Application Number
- CN202511485491.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-17
AI Technical Summary
Existing waterborne emulsions cannot achieve a synergistic improvement in flame retardant properties and film strength after film formation, failing to meet the flame retardant rating and mechanical performance requirements of demanding scenarios. Furthermore, the introduction of flame retardants disrupts the continuity and integrity of the film structure.
A multi-element synergistic flame-retardant waterborne composite emulsion is used. Through the synergistic effect of silicon, phosphorus, nitrogen and boron elements, combined with boron-containing cellulose-based reinforcing agents, a tight interactive network is formed to improve flame retardant performance and enhance mechanical properties.
It significantly improves the flame retardant and mechanical properties of waterborne emulsions, achieving a limiting oxygen index of 33.2%, a vertical burning rating of V-0, a film hardness of 2H, and an adhesion of 5B. It also reduces production costs and is suitable for large-scale industrial production.
Smart Images

Figure CN120966175A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of functional environmental protection emulsion, and particularly relates to a multi-element synergistic flame-retardant water-based composite emulsion as well as a preparation method and application thereof. BACKGROUND
[0002] The water-based composite emulsion has the advantages of low VOC emission, environmental friendliness, convenient construction and the like, and is widely applied in the fields of furniture coatings, architectural decoration, traffic interior decoration and the like, and becomes one of core materials for replacing solvent-based emulsion. However, the existing water-based emulsion generally has the technical bottleneck that the flame-retardant performance and the film strength are difficult to be synergistically improved after film formation, and the main reason is that the limiting oxygen index (LOI) of the film-forming substance is usually lower than 22%, which is easy to ignite and accompanied by molten dripping during combustion, and thus cannot meet the requirements of the flame-retardant grade (such as UL94 V-0 grade, GB 8624 B1 grade) in the fields of building and traffic; meanwhile, the mechanical performance (such as tensile strength < 10 MPa, pencil hardness < HB, adhesion ≥ 2 grade (crosshatch method), elongation at break < 100%) of the film layer is insufficient, and problems such as cracking, scratching and peeling are easy to occur, which seriously limits the application thereof in high requirement scenarios.
[0003] In order to solve the above problems, the existing technology mainly modifies the water-based emulsion by adding flame retardants. At present, the commonly used added flame retardants include phosphorus (P) system, silicon (Si) system, nitrogen (N) system and boron (B) system, but most researchers still use a single flame-retardant element (such as silicon system, phosphorus system or boron system), which leads to the difficulty in achieving the ideal level of flame-retardant effect. The multi-element synergistic flame-retardant system can integrate different flame-retardant mechanisms (solid phase carbonization, gas phase free radical capture, inert gas dilution and the like), and is an effective path for improving the flame-retardant effect. However, the introduction of the flame retardant inevitably destroys the continuity of the emulsion film formation process and the integrity of the film layer structure, leading to the contradiction that the flame-retardant effect and the film strength are in a trade-off relationship. SUMMARY
[0004] In view of the problem that the flame-retardant effect and the film strength of the water-based emulsion are difficult to balance in the prior art, the present application provides a multi-element synergistic flame-retardant water-based composite emulsion. The silicon, phosphorus, nitrogen and boron multiple elements are synergistically flame-retardant, so as to significantly improve the flame-retardant performance of the water-based emulsion, and meanwhile, the introduction of the boron-containing cellulose-based reinforcing agent significantly enhances the mechanical performance of the emulsion on the basis of synergistic flame-retardant.
[0005] One of the technical solutions of the present application is to provide a multi-element synergistic flame-retardant water-based composite emulsion, which comprises the following components: Water-based resin 70 parts by weight, silicon-containing flame retardant 20-25 parts by weight, phosphorus-nitrogen-containing flame-retardant synergist 4-7 parts by weight, boron-containing cellulose-based reinforcing agent 1-3 parts by weight; the water-based resin is a water-based acrylic resin; the silicon-containing flame retardant is sodium silicate; the phosphorus-nitrogen-containing flame-retardant synergist is guanidine phosphate; the solid content of the water-based composite emulsion is 35-45 wt%. The boronized cellulose plays a synergistic flame-retardant role and a reinforcing role in the water-based composite emulsion.
[0006] Sodium silicate, guanidine phosphate and boronized cellulose form a close interaction network in the water-based acrylic emulsion through various forces. Between sodium silicate and guanidine phosphate, the guanidine group of guanidine phosphate is protonated to generate a positively charged -NH3 + in an alkaline condition, forming electrostatic attraction with the silicate negative ions (SiO3 2- ) produced by the hydrolysis of sodium silicate, and the free hydroxyl groups (Si-OH) produced by the hydrolysis of sodium silicate form hydrogen bonds with the boronic acid groups (-B(OH)2) on the surface of boronized cellulose, while the amino groups of guanidine phosphate form N-H…O hydrogen bonds with the hydroxyl groups of cellulose, and the protonated guanidine group also generates electrostatic attraction with the trace negative charge on the surface of cellulose, forming a wide hydrogen bond network. In addition, the two have a synergistic effect in flame retardation - the phosphoric acid (acid source) produced by the decomposition of guanidine phosphate and the boric anhydride (char-forming catalyst) produced by the decomposition of boronized cellulose synergistically catalyze dehydration to form carbon, promoting the formation of a dense carbon layer. Through the combined action of hydrogen bonds and electrostatic attraction, the three form a multi-scale crosslinking network, and the phosphorus-nitrogen system of guanidine phosphate, the boron element of boronized cellulose and the gas source of sodium silicate synergistically achieve efficient intumescent flame retardation, and together impart excellent stability, crosslinking degree and functional properties to the system.
[0007] Further, the boron-containing cellulose-based reinforcing agent is modified boronized cellulose, and its preparation process is as follows: Mix 6 wt% cellulose solution and 0.6 wt% sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to a mass ratio of 1:1 to obtain solution A; by precisely controlling the feeding ratio of cellulose and sodium tetraborate decahydrate, the boron-containing group is modified on the surface of cellulose, so that it has the best flame-retardant and reinforcing effect after being mixed with sodium silicate and guanidine phosphate.
[0008] (2) Adjust the pH of solution A to 10 with NaOH solution to obtain solution B; (3) Perform boronation reaction of solution B in a high-speed stirrer at 400 rpm; (4) After the boronation reaction is completed, vacuum filtration is performed to obtain solid C; (5) Wash solid C with deionized water, and freeze-dry to obtain the boron-containing cellulose-based reinforcing agent.
[0009] Further, the solute in the cellulose solution is one of cellulose nanofiber (CNF), cellulose nanocrystal (CNC) and microcrystalline cellulose (MCC).
[0010] Further, the time of the boronization reaction is 1 h.
[0011] Further, the concentration of the NaOH solution is 0.1 mol / L.
[0012] The second technical solution of the present application provides a preparation method of the above water-based composite emulsion, specifically: the water-based resin, the silicon-containing flame retardant, the phosphorus-nitrogen-containing flame retardant synergist and the boron-containing cellulose-based reinforcing agent are blended by one-step method, water is added to adjust the solid content to 35-45 wt%, and uniform stirring is performed for 1-2 h.
[0013] The third technical solution of the present application provides an application of the above water-based composite emulsion in a flame-retardant material.
[0014] The present application has the following advantages: The present application improves the flame-retardant performance while also improving the mechanical performance. By introducing the boron-containing cellulose-based reinforcing agent (boronized cellulose), the heat resistance of the material is enhanced, and the mechanical performance is also significantly improved. The hardness of the composite emulsion film can reach 2H, and the adhesion can reach 5B.
[0015] (2) By skillfully combining the silicon-containing flame retardant (sodium silicate), the phosphorus-nitrogen-containing flame retardant synergist (guanidine phosphate) and the boron-containing cellulose-based reinforcing agent, the multi-element synergistic flame retardation of the water-based emulsion is realized, thereby significantly improving the overall flame-retardant performance of the emulsion. The limiting oxygen index can be as high as 33.2%, and the vertical combustion experiment reaches the V-0 level.
[0016] (3) The present application adopts a one-step blending preparation method, in which the water-based resin, different flame retardants, synergists and reinforcing agents are mixed in proportion, and the water-based composite emulsion can be prepared by uniform stirring. The process flow is simple and easy to implement, which reduces the production cost and is conducive to large-scale industrial production. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 It is a scanning electron microscope-energy dispersive spectrometer (SEM-EDS) of the boron-containing MCC-based reinforcing agent in Example 3. DETAILED DESCRIPTION
[0018] The following examples are used to further illustrate the present application, and the purpose is to illustrate the present application and should not be interpreted as limiting the scope of the present application. The following uses weight parts and weight percentages unless otherwise specified.
[0019] The raw materials used in the present application are all conventional commercially available products unless otherwise specified; the methods used in the present application are all conventional methods in the art unless otherwise specified.
[0020] In the present application, the limiting oxygen index (LOI) test standard is GB / T 2406.2-2009; the UL-94 test standard is GBT 2408-2008; the hardness test standard is ISO 15184:2012; the adhesion test standard is ASTM D 4541-95 and ISO 4624.
[0021] The embodiments of the present application are further described below in multiple examples.
[0022] It should be clear that the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by a person of ordinary skill in the art based on the embodiments in the present application without making creative efforts fall within the scope of protection of the present application.
[0023] The terms used in the embodiments of the present application are only for the purpose of describing the specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0024] Example 1 (1) 6 wt% of cellulose nanofiber (CNF) solution and 0.6 wt% of sodium tetraborate decahydrate (Na2B4O7•10H2O) solution were mixed in a mass ratio of 1:1 to obtain solution A; (2) The pH of solution A was adjusted to 10 with NaOH solution to obtain solution B; (3) Solution B was stirred at 400 rpm in a high-speed stirrer; (4) After the boronization reaction was completed, solid C was obtained by vacuum filtration; (5) Solid C was washed with deionized water, and boron-containing CNF-based reinforcing agent was obtained after freeze-drying.
[0025] Take 70 parts of water-based acrylic resin, 20 parts of sodium silicate, 7 parts of guanidine phosphate, and 3 parts of boron-containing CNF-based reinforcing agent, add water to control the solid content to 35%, and blend for 1 h by one-step method to obtain a multi-element flame-retardant reinforcing water-based composite emulsion. Then, the mixed water-based composite emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning and mechanical property of the water-based composite emulsion. The results are shown in Table 1.
[0026] Example 2 (1) 6 wt% of cellulose nanocrystal (CNC) solution was mixed with 0.6 wt% of sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to the mass ratio of 1:1 to obtain solution A; (2) The pH of solution A was adjusted to 10 with NaOH solution to obtain solution B; (3) Solution B was stirred at 400 rpm in a high-speed stirrer; (4) After the boronation reaction was completed, solid C was obtained by vacuum filtration; (5) Solid C was washed with deionized water, and boron-containing CNC-based reinforcing agent was obtained after freeze-drying.
[0027] Take 70 parts of water-based acrylic resin, 20 parts of sodium silicate, 7 parts of guanidine phosphate, 3 parts of boron-containing CNC-based reinforcing agent, add water to control the solid content to 35%, and blend for 1 h by one-step method to obtain a multi-element flame-retardant reinforced water-based composite emulsion. Then, the mixed water-based composite emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning and mechanical property of the water-based composite emulsion. The results are shown in Table 1.
[0028] Example 3: (1) 6 wt% of microcrystalline cellulose (MCC) solution was mixed with 0.6 wt% of sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to the mass ratio of 1:1 to obtain solution A; (2) The pH of solution A was adjusted to 10 with NaOH solution to obtain solution B; (3) Solution B was stirred at 400 rpm in a high-speed stirrer; (4) After the boronation reaction was completed, solid C was obtained by vacuum filtration; (5) Solid C was washed with deionized water, and boron-containing MCC-based reinforcing agent was obtained after freeze-drying.
[0029] Take 70 parts of water-based acrylic resin, 20 parts of sodium silicate, 7 parts of guanidine phosphate, 3 parts of boron-containing MCC-based reinforcing agent, add water to control the solid content to 35%, and blend for 1 h by one-step method to obtain a multi-element flame-retardant reinforced water-based composite emulsion. Then, the mixed water-based composite emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning and mechanical property of the water-based composite emulsion. The results are shown in Table 1.
[0030] Example 4: (1) 6 wt% of microcrystalline cellulose (MCC) solution was mixed with 0.6 wt% of sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to the mass ratio of 1:1 to obtain solution A; (2) Adjust the pH of solution A to 10 with NaOH solution to obtain solution B; (3) Stir solution B in a high-speed stirrer at 400 rpm; (4) After the boronization reaction is completed, vacuum filtration is performed to obtain solid C; (5) Wash solid C with deionized water, and freeze-dry to obtain a boron-containing MCC-based reinforcing agent.
[0031] Take 70 parts of water-based acrylic resin, 25 parts of sodium silicate, 4 parts of guanidine phosphate, and 1 part of boron-containing MCC-based reinforcing agent, add water to control the solid content to 45%, and blend for 2 h by one-step method to obtain a multi-element flame-retardant reinforcing water-based composite emulsion. Then, the mixed water-based composite emulsion is applied on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning, and mechanical property of the water-based composite emulsion. The results are shown in Table 1.
[0032] Example 5: (1) Mix 6 wt% microcrystalline cellulose (MCC) solution and 0.6 wt% sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to a mass ratio of 1:1 to obtain solution A; (2) Adjust the pH of solution A to 10 with NaOH solution to obtain solution B; (3) Stir solution B in a high-speed stirrer at 400 rpm; (4) After the boronization reaction is completed, vacuum filtration is performed to obtain solid C; (5) Wash solid C with deionized water, and freeze-dry to obtain a boron-containing MCC-based reinforcing agent.
[0033] Take 70 parts of water-based acrylic resin, 25 parts of sodium silicate, 4 parts of guanidine phosphate, and 1 part of boron-containing MCC-based reinforcing agent, add water to control the solid content to 45%, and blend for 2 h by one-step method to obtain a multi-element flame-retardant reinforcing water-based composite emulsion. Then, the mixed water-based composite emulsion is applied on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning, and mechanical property of the water-based composite emulsion. The results are shown in Table 1.
[0034] Example 6: (1) Mix 6 wt% microcrystalline cellulose (MCC) solution and 0.6 wt% sodium tetraborate decahydrate (Na2B4O7•10H2O) solution according to a mass ratio of 1:1 to obtain solution A; (2) Adjust the pH of solution A to 10 with NaOH solution to obtain solution B; (3) Stir solution B in a high-speed stirrer at 400 rpm; (4) After the boronization reaction is completed, vacuum filtration is performed to obtain solid C; (5) The solid C is washed with deionized water, and then freeze-dried to obtain a boron-containing MCC-based reinforcing agent.
[0035] Take 70 parts of water-based acrylic resin, 25 parts of sodium silicate, 4 parts of guanidine phosphate, and 1 part of boron-containing MCC-based reinforcing agent, add water to control the solid content to 45%, and then blend for 2 h by one-step method to obtain a multi-element flame-retardant reinforcing water-based composite emulsion. Then, the mixed water-based composite emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning, and mechanical properties of the water-based composite emulsion. The sample is tested and characterized, and the results are shown in Table 1.
[0036] Comparative Example 1: Take 70 parts of water-based acrylic resin and 30 parts of sodium silicate, add water to control the solid content to 45%, and then blend for 2 h by one-step method to obtain a flame-retardant water-based composite emulsion. Then, the mixed water-based composite emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning, and mechanical properties of the water-based composite emulsion. The sample is tested and characterized, and the results are shown in Table 1.
[0037] Comparative Example 2: In the example 6, the boron-containing MCC-based reinforcing agent is replaced by boric acid. The mixed water-based emulsion is coated on the surface of wood for application, and further prepared into a sample for testing the limiting oxygen index, UL-94 vertical burning, and mechanical properties of the water-based composite emulsion. The sample is tested and characterized, and the results are shown in Table 1.
[0038] Table 1: Performance test results of each example
[0039] According to the results in Table 1, it is found that the synergistic effect of multiple flame-retardant elements can effectively improve the flame-retardant performance of the water-based composite emulsion. When 7 parts of phosphorus-nitrogen synergistic agent are added, and 3 parts of boron-containing CNF-based reinforcing agent are added, the oxygen index of the sample can be as high as 33.2%, and the UL-94 rating of the sample coated with the water-based composite emulsion can reach V-0 level from NR level. In addition, when the amount of boron-containing cellulose-based reinforcing agent is 3 parts, the limiting oxygen index of the sample is slightly higher than that when the amount of boron-containing cellulose-based reinforcing agent is 1 part. The above results show that the addition of phosphorus-nitrogen synergistic agent promotes the dispersion of the flame-retardant agent through multiple interactions, and achieves better flame-retardant effect.
[0040] Meanwhile, the water-based composite emulsion film hardness of the silicon-containing flame retardant, phosphorus-nitrogen-containing synergist and boron-containing cellulose-based reinforcing agent modified by blending in a certain proportion is increased: when the boron-containing cellulose-based reinforcing agent is 3 parts, the hardness grade of the sample reaches 2H, and when the boron-containing cellulose-based reinforcing agent is 1 part, the water-based composite emulsion film hardness reaches 3H. Compared with Comparative Example 1, the adhesion grade of the sample is increased to 5B; and in Comparative Example 2, the adhesion of the sample after replacing the boron-containing cellulose-based reinforcing agent with boric acid is still maintained at 4B, without the reinforcing effect. The above results all show that the addition of the boron-containing cellulose-based reinforcing agent helps to improve the water-based composite emulsion film mechanical properties.
[0041] The above examples illustrate the structure, features and effects of the present application. The above description is only the preferred embodiment of the present application. Any changes or modifications made in accordance with the concept of the present application, or equivalent embodiments with equivalent changes, shall be within the scope of the present application.
Claims
1. A multi-element synergistic flame-retardant aqueous composite emulsion, characterized in that, It includes the following components: The water-based resin comprises 70 parts by weight, a silicone flame retardant comprising 20-25 parts by weight, a phosphorus-nitrogen flame retardant synergist comprising 4-7 parts by weight, and a boron-cellulose-based reinforcing agent comprising 1-3 parts by weight; the water-based resin is a water-based acrylic resin. The silicon-containing flame retardant is sodium silicate; the phosphorus-nitrogen-containing flame retardant synergist is guanidine phosphate; and the solid content of the aqueous composite emulsion is 35-45 wt%.
2. The aqueous composite emulsion according to claim 1, characterized in that, The boron-containing cellulose-based reinforcing agent is a modified boronized cellulose, and its preparation process includes: mixing a cellulose solution and a sodium tetraborate decahydrate solution at a mass ratio of cellulose to sodium tetraborate decahydrate of 10:1, adjusting the pH to 10, and carrying out a boronization reaction under stirring conditions; after the boronization reaction is completed, vacuum filtration is performed to obtain a solid, which is then freeze-dried to obtain the boron-containing cellulose-based reinforcing agent.
3. The aqueous composite emulsion according to claim 2, characterized in that, The solute in the cellulose solution is one of cellulose nanofibers, cellulose nanocrystals, or microcrystalline cellulose.
4. The aqueous composite emulsion according to claim 2, characterized in that, The cellulose solution has a mass fraction of 6 wt%, and the sodium tetraborate decahydrate solution has a concentration of 0.6 wt%.
5. The aqueous composite emulsion according to claim 2, characterized in that, The stirring speed was 400 rpm, and the borylation reaction time was 1 h.
6. The aqueous composite emulsion according to claim 2, characterized in that, pH was adjusted using a 0.1 mol / L NaOH solution.
7. A method for preparing the aqueous composite emulsion as described in claim 1, characterized in that, The water-based resin, silicon-containing flame retardant, phosphorus-nitrogen flame retardant synergist, and boron-containing cellulose-based reinforcing agent are mixed in one step and stirred evenly for 1-2 hours.
8. The application of the aqueous composite emulsion as described in claim 1 in flame retardant materials.
Citation Information
Patent Citations
Multifunctional coatings and preparation method thereof
CN101386719A
Intumescent phosphorus-containing grafted polymer flame retardant as well as preparation and application thereof
CN104448326A
Preparation method of high-transparency efficient flame-retardant nano-fibrillated cellulose
CN111662392A
Emulsion composition containing hydrophobically modified cellulose fibers
CN114206994A
Suspensions of water soluble polymers in surfactant free non-aqueous solvents
US20020019318A1